PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA DIMEDIASI KEPUASAN KERJA (Studi pada Guru SD di Dabin II Kecamatan Batangan Kabupaten Pati) - Surati, Surati (Students Journal of Economic and Management, 2012)
This study aimed to analyze the effect of Work Motivation and Discipline to Performance by Mediation Job Satisfaction. The population used in this study is the object of all primary school teachers in Dabin II Subdistrict Batangan Pati Regency totaling 85 people. In this study using primary data obtained by questionnaire. The research method using a computerized approach to program SPSS (Statistics Package for Social Science). The data analysis method used is linear regression to test the effect of mediation. Research shows that the ability of the model to correctly describe the effect of variable Motivation and Discipline Working on Job Satisfaction in the amount of 27.6%. While the other is equal to 73.4% is explained by the variables outside the model The Effect of Motivation, Discipline of Work and Job Satisfaction to Performance 34.2%, and the other at 65.8% outside of the model described in this regression. Motivation Job Satisfaction with mediation does not affect the performance of teachers in Dabin II Subdistrict Batangan Pati Regency. The test results of mediation explained that the direct effect is greater than the indirect effect, ie 0.0125 <0.000324. Discipline Work with Job Satisfaction mediation proved significant effect on performance Dabin II Subdistrict Batangan Pati Regency. The test results prove the value of the indirect effect is greater than the value that is equal to the direct effect of 0.252> 0.098. The results of the analysis could be concluded that the motivations no effect on Job Satisfaction, Motivation also has no effect on performance. Work Discipline positive influence on job satisfaction, job Discipline is also a positive effect on performance. Keywords: Motivation, Discipline Work, Job Satisfaction, and Performance.